EFFECT OF COMPANY SIZE, DEBT POLICY, PROFITABILITY, AND DIVIDEND POLICY ON COMPANY VALUE - Elia Maretha Siagian; Teng Sauh Hwee; Norma Uli Br. Sitohang (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This research was conducted to obtain information about four factors that influence the size of the company's value, the first is the size of the company, the second is the policy taken in debt, the third is the amount of profit, and the last is the policy in distributing dividends to shareholders. In order to make it easier to review and analyze data related to the themes studied in this research, researchers use quantitative methods. Data displayed is related to companies engaged in the basic and chemical industrial sectors between 2018 and 2020. A total of 78 companies were designated as the population in this research, of which 40 companies were sampled. Analysis test using the T test got different results for each variable. One variable, namely the size of the company does not have an impact on the value of the company, while the other three variables have an impact on the value of the company. Results obtained from the adjusted R Square test obtained the number 0.898, with these results providing information that all independent variables have an influence of 89.8% on firm value and 10.2% is influenced by other variables